Environment Context Variability and Incidental Word Learning: A Virtual Reality Study - Francisco Rocabado; Jorge González Alonso; Jon Andoni Duñabeitia (Brain Sciences, 2022)
Previous research has shown that changes in the scenarios in which something is learned and recalled, respectively, may result in a subpar performance in memory recollection. The current study aimed to evaluate how changes in the visuo-perceptual environmental learning context impact incidental vocabulary learning. To this end, a highly immersive virtual reality setting was created, and participants were required to read eight distinct stories visually presented to them. A novel word was delivered twice in every paragraph and embedded in each story. Stories could be displayed either in a high variability condition, where each paragraph was shown in a new environment context (four different classrooms) or in a low variability condition, where each paragraph was shown in the same context. The findings obtained across four assessment tasks (free recall, recognition, picture matching, and sentence completion) demonstrated that significant visuo-perceptual variability did not bring about any disadvantages in word learning. Thus, perceptual information from a physically diverse environment could provide a variety of instructional and educational beneficial possibilities in the absence of a learning disadvantage.